THE SENSORY CHARACTERISTICS OF FISH OIL IN TUNA HEAD (Thunnus albacares) - Panji Yaversio; Mirna Ilza; Andarini Diharmi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2021)
ABSTRACTThis study aimed to determine the sensory characteristics of fish oil in tuna head (Thunnus albacares) in tuna fish head oil rendered at different temperatures (60, 70, and 80 °C). The research was carried out in several steps, including: preparingthe sample, measuring the fat content, extracting the fish oil intuna head by using the wet rendering method, and assessing the sensory value of the fish oil. The results showed that the head of tuna was containing fish oil of 8.29%. Based on the sensory evaluation, it could be concluded that the lower the extraction temperature, the clearer the fish oil color produced. Keywords:Thunnus albacares, temperature, sensory, tuna head, fish oil